Resistance of Common Bean Cultivar AB 136 to races 31 and 69 of colletotrichum lindemuthianum: the Co-6 Locus - Vidigal, Maria Celeste Gonçalves; Sakiyama, Ney S.; Vidigal Filho, Pedro S.; Amaral Júnior, Antônio T.; Poletine, Juliana Parisotto; Oliveira, Valter R. (Crop Breeding and Applied Biotechnology, 2001)
Genetic resistance in common bean (Phaseolus vulgaris L.) is the most effective control of anthracnosecaused by Colletotrichum lindemuthianum (Sacc. et Magnus) Lams.-Scrib. In a previous report, two geneticsymbols, Q and B, were assigned to describe the gene(s) controlling the resistance of the cultivar AB 136 toraces 31 and 69 of the pathogen, respectively. In the present study, progeny tests with two identical sets of F2:3population were used to obtain the first experimental evidence whether one single gene controls the resistanceto both races 31 and 69. The absence of recombinations between the putative genes (Q and B) allowed theconclusion that a single dominant gene controls the resistance of the cultivar AB 136 to both races 31 and 69.The symbol Co-6 was assigned to the gene. In addition, linkage analysis with RAPD marker indicated that Co-6 also controls the resistance of AB 136 to other races of the pathogen, or that different genes are present inthe same linkage block.
Keywords: Disease resistance; Breeding